دراسة التدرج الحبيبي لخمس مصادر من الركام الخشن في الجبل الغربي (Comprehensive Journal of Science, 2026)
The properties of aggregates greatly affect the strength and behavior of the concrete structure, and one of the important properties of concrete aggregates is its granularity, for the purpose of obtaining a dense concrete structure, it must be an appropriate gradation in the aggregate, gradation of aggregates is an important factor in controlling the workability of soft concrete. when determining the amount of aggregate present in a unite volume of concrete, the workability of the mixture is more than the aggregate gradation is appropriate. Thus the need for a mount of water is less in turn, and this leads to an increase in the resistance of the resulting concrete, and it also affects the total cost of concrete. On that basis, we conducted a survey of five regions in the western mountains (Libyan west), we were bringing some sources of rubble from it, to study their suitability for use. As preparation for advanced tests of concrete, in addition to achieving the economic requirements and long-term strength of concrete, and knowing its granular gradation each region contained three gradations of aggregates, and then mixing the granular gradient for each region with three gradations as on attempt to know the behavior and compare it with other regions.